ZrO2-doped reinforced cold-sintered ZnO voltage-sensitive ceramic and preparation method thereof
By employing a low-temperature sintering process that combines ZrO2 doping and annealing, the problem of high-temperature sintering of ZnO-based varistors was solved, enabling the preparation of low-energy-consumption, high-performance ZnO varistors with excellent nonlinear coefficients and breakdown field strength.
Patent Information
- Application Number
- CN202511706413.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-20
- Publication Date
- 2026-01-27
AI Technical Summary
Existing high-temperature sintering processes for ZnO-based varistors suffer from problems such as high energy consumption, abnormal grain growth, unstable grain boundary barriers, and dopant volatilization, making it difficult to achieve green manufacturing and high-performance preparation.
A low-temperature sintering process enhanced by ZrO2 doping and synergistic annealing is adopted. By introducing ZrO2 into the ZnO matrix, its grain boundary pinning effect and high stability are utilized. Combined with cold sintering of acetic acid solution and medium-temperature annealing, a stable grain boundary phase structure is formed, which reduces the sintering temperature and suppresses dopant volatilization.
A stable grain boundary barrier was formed at a lower temperature, significantly reducing energy consumption, improving the nonlinear coefficient and breakdown field strength of the material, and obtaining high-performance, stable ZnO varistor ceramics.
Smart Images

Figure CN121405459A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing ZnO ceramics, and particularly to a doping modification and low-temperature sintering preparation technique for ZnO-based varistors. Technical Background
[0002] ZnO-based varistors are widely used in overvoltage protection of power systems and electronic equipment due to their typical nonlinear current-voltage characteristics and excellent surge suppression capabilities. Their performance is highly dependent on microscopic factors such as grain size, grain boundary barrier structure, and phase composition stability. Therefore, microstructure control has always been the core of varistor research. Traditional ZnO varistors generally use high-temperature solid-state sintering processes above 1100℃ to complete densification and grain boundary phase formation. However, high-temperature sintering has three prominent technical bottlenecks: (1) Under high temperature, grains are prone to abnormal growth, which reduces the number of grain boundaries and the height of the potential barrier, resulting in a decrease in nonlinear characteristics; (2) Low-melting-point additives such as Bi2O3 volatilize significantly at high temperatures, causing instability in grain boundary composition and reducing breakdown strength and long-term reliability; (3) High-temperature sintering consumes a lot of energy and has high carbon emissions, which is not conducive to the green manufacturing of varistors.
[0003] To address the energy consumption and grain runaway issues caused by high-temperature sintering, the Cold Sintering Process (CSP) has emerged in recent years. This process utilizes the dissolution-precipitation mechanism initiated by organic acid solutions (such as acetic acid) to achieve preliminary densification of ceramic green bodies within the range of 200–300℃, effectively suppressing grain growth. However, existing cold sintering technologies still have the following limitations: (1) It is difficult to form a complete grain boundary barrier by cold sintering alone. At low temperatures, amorphous phases or incomplete interface structures are easily left between ZnO grains, making it impossible to establish a typical double Schottky barrier, resulting in excessive leakage current and insufficient nonlinear coefficient. (2) It still requires heat treatment at a relatively high temperature (about 900℃). Although the current heat treatment-assisted cold sintering technology is cooler than traditional solid-state sintering, it still usually requires ≥850℃ to achieve grain boundary reconstruction, remove residual organic matter, and promote the formation of Bi2O3 grain boundary phase, resulting in high energy consumption. (3) Dopants still face the risk of volatilization above 850℃. Even if the temperature is lower than the traditional sintering temperature of 1100℃, doped oxides such as Bi2O3 and Co2O3 will still volatilize or decompose in the 850-900℃ range, causing the grain boundary phase ratio to shift and affecting the stability of the potential barrier. (4) Grain growth is still difficult to control effectively. Although cold sintering inhibits the initial grain growth, the grains may still grow rapidly again during heat treatment at 850-900℃, resulting in a decrease in the potential gradient.
[0004] Materials science research shows that the introduction of thermally stable secondary phase particles can effectively hinder grain migration and merging through the zener pinning mechanism, thereby reducing the overall energy barrier for crystal growth. Among them, ZrO2 has the characteristics of high melting point, high chemical stability, and poor solid solution. It is a typical secondary phase particle in ZnO matrix and can produce the following mechanisms: (1) Zener pinning: ZrO2 particles can physically hinder the migration of ZnO grain boundaries, making it difficult for grains to grow during heat treatment; (2) Lowering the densification energy barrier: By inhibiting grain merging, densification is made more dependent on diffusion and the disappearance of pores than grain growth, thereby reducing the heat energy required for sintering; (3) Stabilizing the grain boundary chemical environment: ZrO2 exists stably at lower temperatures and does not participate in volatilization or decomposition, which helps to inhibit the loss of components such as Bi2O3; (4) Delaying abnormal aggregation of grain boundary phases: Controlling the grain boundary movement speed allows the amorphous interface after cold sintering to be gradually reconstructed at lower temperatures.
[0005] Therefore, by fully utilizing the fine grain control effect of ZrO2, it is possible to further reduce the heat treatment temperature while ensuring the formation of grain boundary barriers, lowering it from 850–900℃ in the traditional cold sintering system to an even lower temperature range, thereby reducing energy consumption and improving microstructure stability. Thus, developing a ZnO varistor ceramic preparation route that achieves low-temperature grain pinning, suppresses dopant volatilization, and synergistically reduces the heat treatment temperature through cold sintering is of significant practical importance for improving the green and high-performance preparation of ZnO varistors. Summary of the Invention
[0006] The purpose of this invention is to provide a method for cold sintering ZnO varistor ceramics with ZrO2 doping enhancement, so as to obtain ZnO varistor ceramics with excellent varistor properties, high stability and economical preparation.
[0007] The technical solution adopted by the present invention to solve the above-mentioned technical problems is: a method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the method comprising the following steps:
[0008] S1: Prepare an acetic acid solution using distilled water and glacial acetic acid, wherein the acetic acid concentration is 1-4 mol%.
[0009] S2: The initial ZnO powder is mixed with metal oxide dopants consisting of ZnO, Bi2O3, Co2O3, Mn2O3, Cr2O3, NiO, CaO and ZrO2 in the following ratio: (94.3-x)wt% ZnO-1.5wt% Bi2O3-1wt% Co2O3-1wt% Mn2O3-0.5wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-xZrO2 to form the precursor powder, where x is the mass percentage and the value of x is 0-3.6.
[0010] S3: The precursor powder prepared in S2 is then mixed with the acetic acid solution, and after grinding and dispersing, a mixed slurry is obtained, wherein the amount of acetic acid solution added is 10-40 wt% of the precursor powder mass.
[0011] S4: Place the mixed slurry into a steel mold, apply a pressure of 100-500MPa, and cold sinter at 200-300℃ for 0.5-3 hours.
[0012] S5: Anneal the cold-sintered sample at a temperature of 650-850℃ for 4-10 hours to obtain ZnO-based varistors.
[0013] As an improvement, the heating rate of the S5 cold sintering is 1-10℃ / min.
[0014] As an improvement, the heat treatment temperature of S5 is 700-850℃.
[0015] Compared with the prior art, the present invention has at least the following advantages:
[0016] (1) ZrO2 doping and annealing synergistically construct a low-energy-consumption, low-temperature sintering system, achieving high density and excellent structural stability. This invention introduces 0-3.6 wt% ZrO2 into the ZnO precursor system and uses acetic acid solution to construct a controllable liquid phase environment, achieving low-temperature densification of the green body under conditions of 100-500 MPa and 200-300 °C. The interfacial modulation effect of ZrO2 enhances solid-phase diffusion, enabling the ceramic to achieve a stable initial structure at sintering temperatures far below the traditional ≥1100 °C, while significantly reducing grain coarsening. Compared with high-temperature sintering processes, this approach significantly reduces energy consumption, thermal stress, and improves the mechanical integrity of the green body.
[0017] (2) The sintering temperature of this invention is further reduced from approximately 900°C, commonly found in traditional heat treatment-assisted cold sintering, to approximately 750°C, significantly reducing sintering energy consumption and suppressing dopant volatilization. Through the synergistic effect of ZrO2 grain boundary pinning and medium-temperature annealing, this invention can complete grain boundary reconstruction and barrier establishment at a lower temperature range of approximately 750°C, avoiding the bottleneck in existing cold sintering systems that require processing in the 850-900°C range to form stable grain boundaries. This temperature reduction not only significantly reduces energy consumption during the sintering stage but also effectively suppresses the volatilization of low-melting-point dopants such as Bi2O3 and Co2O3, achieving a more stable grain boundary chemical composition and electrical performance basis.
[0018] (3) The interface modulation effect of ZrO2 enhances the grain boundary barrier capability and reduces leakage current. ZrO2 has high dielectric stability and interface compatibility. After being dispersed in the grain boundary region, it can enhance the electron trapping capability, widen the depletion layer, and increase the grain boundary barrier height, thereby achieving significant leakage current suppression under low electric field. The structurally stable grain boundary barrier formed by this invention enables the ceramic to exhibit low leakage current (<20μA) and improves the long-term voltage stability and reliability of the varistor.
[0019] (4) The Zener pinning effect of ZrO2 inhibits grain growth, increases grain boundary density, and enhances the varistor nonlinearity of the material. ZrO2 exists as a difficult-to-solidify and highly stable second phase in ZnO crystals, which can generate significant grain boundary pinning during cold sintering and annealing, effectively hindering grain boundary migration and grain agglomeration, while suppressing the high-temperature volatilization of Bi2O3 and avoiding grain boundary phase imbalance. As a result, this invention obtains a fine-grained structure with an average grain size of approximately 1.414 μm, high grain boundary density, and uniform barrier distribution, thereby achieving a high breakdown field strength of 713 V / mm and an excellent nonlinear coefficient α of 45.75, exhibiting comprehensive performance superior to traditional high-temperature solid-state methods. Attached Figure Description
[0020] Figure 1 XRD phase identification for ZrO2 under different doping conditions.
[0021] Figure 2 Comparison of grain morphology before and after annealing and ZrO2 doping.
[0022] Figure 3 Average grain size and packing density of ZrO2 samples with different doping.
[0023] Figure 4 JE curves of ZrO2 samples with different doping. Detailed Implementation
[0024] The present invention will now be described in further detail.
[0025] This invention proposes a ZrO2-doped synergistic annealing enhanced low-temperature sintering process for high-performance ZnO-based varistors. Traditional ZnO-based varistors often rely on high-temperature sintering at 1100–1300℃, which has significant shortcomings in terms of abnormal grain growth, Bi2O3 volatilization, unstable grain boundary barriers, and fluctuating electrical properties. While cold sintering technology can achieve preliminary densification at ≤300℃, it is limited by insufficient grain boundary activation and incomplete liquid-phase reaction, making it difficult to meet the requirements of varistors for barrier integrity and electrical performance. Therefore, this invention, by introducing an appropriate amount of ZrO2 and combining it with a composite process of low-temperature cold sintering and annealing, achieves overall improvement in grain structure control, grain boundary phase stabilization, and electrical performance at even lower processing temperatures.
[0026] This research addresses the problems of poor compatibility between ZrO2 doping and processing techniques, and limited grain control effects in existing technologies. It achieves precise suppression of ZnO grain growth to obtain a uniform and fine grain structure. It also solves the problem of insufficient grain boundary barrier optimization, improving the electron trapping ability at grain boundaries to reduce leakage current and enhance the stability of the varistor voltage. Furthermore, it addresses the issues of high energy consumption in high-temperature sintering and insufficient synergy between cold sintering and annealing by constructing a low-temperature synergistic sintering process adapted to the ZrO2 doping system to improve the compactness of the green body and reduce energy consumption. Finally, it solves the problem of Bi2O3 volatility at high temperatures by utilizing the high stability of ZrO2 and the grain boundary pinning effect to suppress Bi2O3 volatilization, ensuring stable grain boundary phase composition and maintaining grain boundary barrier performance. Additionally, it addresses the issue of phase structure control by further optimizing the overall ceramic performance through the synergy of doping amount and annealing process, ultimately obtaining a ZnO varistor ceramic with excellent varistor characteristics, high stability, and economical preparation.
[0027] The core of this process lies in the fact that ZrO2 easily accumulates at the ZnO grain boundaries during sintering, forming an effective pinning effect that significantly inhibits abnormal grain growth and further reduces the heat treatment temperature to 750℃, while also greatly reducing the volatilization rate of Bi2O3 under high-temperature conditions. Through the formation of the Zr–Bi–O composite structure at the grain boundaries, the liquid phase of Bi2O3 remains continuous and stable during the annealing stage, making the grain boundary barrier more complete and uniform, thereby improving electron trapping ability and barrier height, reducing leakage current, and increasing the nonlinear coefficient. Furthermore, this invention utilizes cold sintering to achieve uniform powder packing and initial densification, followed by annealing at 650–850℃ to stimulate grain boundary diffusion and liquid phase rearrangement, further enhancing the ZrO2 doping effect and forming a fine, uniform microstructure with a stable grain boundary phase. The ZnO-based varistor ceramic prepared by this invention has a nonlinear coefficient of up to 45.75, a breakdown field strength of 713V / mm, and an average grain size of 1.414μm, which surpasses the performance of existing commercial resistor products and has significant energy-saving advantages.
[0028] Example 1: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0029] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0030] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 93.8wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-0.5wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 40wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 100MPa is applied, and cold sintering is carried out at 300℃ for 1 hour.
[0031] (3) Annealing assistance: The cold-sintered sample is transferred into a muffle furnace and heated to 650°C at a heating rate of 1°C / min. It is held for 4 hours to obtain high-density ZnO ceramic, namely sample 1.
[0032] Example 2: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0033] (1) Prepare a 3 mol% acetic acid solution with distilled water and glacial acetic acid.
[0034] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 93.5wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-0.8wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 40wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 200MPa is applied, and cold sintering is carried out at 300℃ for 2 hours.
[0035] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 700°C at a heating rate of 3°C / min. The temperature was held for 4 hours to obtain high-density ZnO ceramic, namely sample 2.
[0036] Example 3: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0037] (1) Prepare a 3 mol% acetic acid solution with distilled water and glacial acetic acid.
[0038] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 94.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-0wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 10wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300MPa is applied, and cold sintering is carried out at 300℃ for 2 hours.
[0039] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 750°C at a heating rate of 5°C / min. The temperature was held for 5 hours to obtain high-density ZnO ceramic, namely sample 3.
[0040] Example 4: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0041] (1) Prepare a 2 mol% acetic acid solution with distilled water and glacial acetic acid.
[0042] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 94.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-0wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 25wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 400MPa is applied, and cold sintering is carried out at 300℃ for 2 hours.
[0043] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 5°C / min. The temperature was held for 5 hours to obtain high-density ZnO ceramic, namely sample 4.
[0044] Example 5: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0045] (1) Prepare a 3 mol% acetic acid solution with distilled water and glacial acetic acid.
[0046] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 93.5wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-0.8wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 40wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 500MPa is applied, and cold sintering is carried out at 250℃ for 3 hours.
[0047] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 650°C at a heating rate of 7°C / min. The temperature was held for 7 hours to obtain high-density ZnO ceramic, namely sample 5.
[0048] Example 6: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0049] (1) Prepare a 1 mol% acetic acid solution with distilled water and glacial acetic acid.
[0050] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 93.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-1wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 20wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300MPa is applied, and cold sintering is carried out at 250℃ for 3 hours.
[0051] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 650°C at a heating rate of 1°C / min. The temperature was held for 4 hours to obtain high-density ZnO ceramic, namely sample 6.
[0052] Example 7: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0053] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0054] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 92.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-2wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 15wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300MPa is applied, and cold sintering is carried out at 250℃ for 3 hours.
[0055] (3) Annealing assistance: The cold-sintered sample is transferred into a muffle furnace and heated to 700°C at a heating rate of 5°C / min. It is held for 5 hours to obtain high-density ZnO ceramic, namely sample 7.
[0056] Example 8: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0057] (1) Prepare a 5 mol% acetic acid solution with distilled water and glacial acetic acid.
[0058] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 91.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-3wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 20wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300MPa is applied, and cold sintering is carried out at 300℃ for 1 hour.
[0059] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 650°C at a heating rate of 5°C / min. The temperature was held for 6 hours to obtain high-density ZnO ceramic, namely sample 8.
[0060] Example 9: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0061] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0062] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 93.5wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-0.8wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 30wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300MPa is applied, and cold sintering is carried out at 300℃ for 1 hour.
[0063] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 850°C at a heating rate of 10°C / min. The temperature was held for 6 hours to obtain high-density ZnO ceramic, namely sample 9.
[0064] Example 10: A method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0065] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0066] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 93.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-1wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 40wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 400MPa is applied, and cold sintering is carried out at 200℃ for 0.5 hours.
[0067] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 770°C at a heating rate of 1°C / min. The temperature was held for 7 hours to obtain high-density ZnO ceramic, namely sample 10.
[0068] Example 11, a method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0069] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0070] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 92.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-2wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 30wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 500MPa is applied, and cold sintering is carried out at 200℃ for 1 hour.
[0071] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 5°C / min. The temperature was held for 8 hours to obtain high-density ZnO ceramic, namely sample 11.
[0072] Example 12, a method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0073] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0074] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 92.1wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-2.2wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 30wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 250MPa is applied, and cold sintering is carried out at 250℃ for 1 hour.
[0075] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 800°C at a heating rate of 10°C / min. The temperature was held for 9 hours to obtain high-density ZnO ceramic, namely sample 12.
[0076] Example 13, a method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0077] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0078] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 91.3wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-3wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 30wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 350MPa is applied, and cold sintering is carried out at 250℃ for 2.5 hours.
[0079] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 850°C at a heating rate of 5°C / min. The temperature was held for 7 hours to obtain high-density ZnO ceramic, namely sample 13.
[0080] Example 14, a method for ZrO2 doping synergistic annealing enhanced low-temperature sintering process, the process steps of which include:
[0081] (1) Prepare a 4 mol% acetic acid solution with distilled water and glacial acetic acid.
[0082] (2) Low-temperature sintering step: The initial ZnO powder is mixed with 90.7wt% ZnO-1.5wt% Bi2O3-1.00wt% Co2O3-1.0wt% Mn2O3-0.50wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-3.6wt% ZrO2 raw powder weighed according to the aforementioned stoichiometric ratio to prepare a precursor powder, and then mixed with 30wt% acetic acid solution. After grinding and dispersing, a mixed slurry is obtained. The mixed slurry is then placed in a steel mold, a pressure of 300MPa is applied, and cold sintering is carried out at 300℃ for 1 hour.
[0083] (3) Annealing assistance: The cold-sintered sample was transferred into a muffle furnace and heated to 850°C at a heating rate of 5°C / min. The temperature was held for 10 hours to obtain high-density ZnO ceramic, namely sample 14.
[0084] Performance tests were performed on ZnO-based varistor ceramic samples prepared in some of the embodiments:
[0085] Figure 1 XRD diffraction patterns of ZrO2 with different dopants showed that no ZrO2 diffraction peaks were detected in the samples after cold sintering and annealing. This indicates that appropriate doping of ZrO2 does not change the crystal structure, but rather it is stably distributed in a highly dispersed state in the ZnO grain boundary region, without forming detectable independent diffraction peaks. This distribution is beneficial for constructing a uniform grain boundary composite structure and effectively improves the material's barrier uniformity. Figure 2A comparison of the grain morphology before and after annealing and doping with 2wt% ZrO2 clearly shows that the annealed cold-sintered ceramic exhibits a distinct grain structure, while the amorphous and molten regions observed in the original cold-sintered sample have completely disappeared. All samples exhibit a dense and uniform microstructure, with abundant Bi-rich intergranular phases distributed along the grain boundaries. These Bi-rich phases can suppress Bi2O3 volatilization and improve the electrical performance of the ZnO varistor. This can be seen from... Figure 4 As can be seen from the JE figure, the Zr-2wt% sample exhibits the best electrical properties, with an α value of 45.75. Figure 3 The average grain size and packing density of the partially doped ZrO2 sample are significantly lower than those of conventionally sintered samples, which have a density of only 5.432 g / cm³. 3 Cold sintering not only significantly reduces the required sintering temperature but also improves densification. These results confirm that cold sintering not only significantly reduces the required sintering temperature but also improves densification. This improvement is because the cold-sintered samples have already undergone partial densification and can be fully sintered with relatively low heat energy. Furthermore, the average grain size gradually decreases with increasing ZrO2 doping concentration, indicating that the addition of ZrO2 effectively suppresses grain growth, mainly due to the lower annealing temperature and the grain boundary pinning effect induced by ZrO2. Figure 4 The JE curves for partially doped ZrO2 samples show that the breakdown field strength increases significantly with increasing ZrO2 doping amount. This is mainly because ZrO2 inhibits grain growth. Adding an appropriate amount of ZrO2 can significantly improve the nonlinear coefficient α.
[0086] Table 1 shows the performance of the samples obtained in Examples 1-14.
[0087]
Claims
1. A method for cold-sintering ZnO varistors reinforced with ZrO2 doping, characterized in that, The method includes the following steps: S1: Prepare an acetic acid solution using distilled water and glacial acetic acid, wherein the acetic acid concentration is 1-4 mol%. S2: Initial ZnO powder is mixed with metal oxide dopants containing ZrO2 in the following proportions: (94.3-x)wt% ZnO-1.5wt% Bi2O3-1wt% Co2O3-1wt% Mn2O3-0.5wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-xZrO2 to form precursor powder, where x is the mass percentage and the value of x is 0-3.
6. S3: The precursor powder prepared in S2 is then mixed with acetic acid solution, and after grinding and dispersing, a mixed slurry is obtained, wherein the amount of acetic acid solution added is 10-40 wt% of the precursor powder mass. S4: Place the mixed slurry into the mold, apply a pressure of 100-500MPa, and cold sinter at 200-300℃ for 0.5-3 hours; S5: Anneal the cold-sintered sample at a temperature of 650-850℃ for 4-10 hours to obtain ZnO-based varistors.
2. The method for ZrO2 doping synergistic annealing to enhance low-temperature sintering process according to claim 1, characterized in that, The composition formula of the precursor powder is: (94.3-x)wt% ZnO-1.5wt% Bi2O3-1wt% Co2O3-1wt% Mn2O3-0.5wt% Cr2O3-1.2wt% NiO-0.5wt% CaO-xZrO2, where x is the mass percentage and the value of x is 0-3.
6.
3. The method for enhancing the low-temperature sintering process by ZrO2 doping synergistic annealing according to claim 1, characterized in that, The heating rate of the S5 cold sintering is 1-10℃ / min.
4. The method for enhancing the low-temperature sintering process by ZrO2 doping synergistic annealing according to claim 1, characterized in that, The heat treatment temperature for S5 is 700-850℃.
5. A ZnO-based varistor ceramic, characterized in that: It was prepared by the ZrO2 doping synergistic annealing enhanced low-temperature sintering process described in any one of claims 1-4.